The influence of urban morphological changes on pluvial flooding during urban expansion - Yue Zhu; Paolo Burlando; Ye Zhang; Dengkai Chi; Jing Wang; Yeshan Qiu; Matteo Bonatesta; Wenyue Zou; Christian Geiß; Puay Yok Tan; Simone Fatichi (Sustainable Cities and Society, 2025)

Long-term hydrological budget over urban areas: approaches and challenges - Yexia Lin Xu; Naika Meili; Simone Fatichi (Journal of Hydrology, 2025)

An Integrated Modelling Framework to Determine Terrestrial Carbon Dioxide Removal via Enhanced Rock Weathering - Ziyan Zhang; Gregory Jones; Salvatore Calabrese; Matteo Bertagni; Simone Fatichi; Bonnie Waring; Athanasios Paschalis (Global Change Biology, 2025)
Enhanced rock weathering (ERW) is an emerging carbon dioxide removal (CDR) strategy that can support net‐zero emission targets. However, current ERW modelling efforts rely on assumptions that introduce substantial variation in CDR estimates across varying ecosystems and hydroclimatic conditions. They typically ignore or oversimplify plant–soil interactions and high‐frequency hydrological dynamics, obscuring short‐term weathering responses and biotic feedbacks to soil moisture dynamics. Here, we introduce an integrated, process‐based modelling framework, T&C‐SMEW, which represents ecohydrological and ERW dynamics, along with microbially explicit biogeochemical processes. We compared framework simulations against a controlled mesocosm experiment and long‐term field observations, demonstrating its ability to reproduce feedstock cation release, soil pH dynamics, gross primary production, and CO 2 fluxes. T&C‐SMEW reveals hydrological constraints and vegetation effects on ERW‐mediated CDR by quantifying impacts on ecosystem respiration, net ecosystem exchange, and alkalinity export, emphasising the importance of ecohydrological modelling for ecosystem‐level CDR estimation. These advances provide a modelling framework for identifying optimal deployment scenarios to establish ERW as a viable and operationally feasible CDR approach.

VIC-Res Mekong: An open-source hydrological-water management model for the Mekong River basin - Hisham Eldardiry; Shanti Shwarup Mahto; Simone Fatichi; Stefano Galelli (Environmental Modelling & Software, 2025)

Future glacier retreat and forest expansion in the Swiss Alps provide limited benefits for carbon sinks - Fuxiao Jiang; Simone Fatichi; Gianalberto Losapio; Nadav Peleg (Agricultural and Forest Meteorology, 2025)

Investigating the influence of urban morphology on pluvial flooding: Insights from urban catchments in England (UK) - Yue Zhu; Paolo Burlando; Puay Yok Tan; Jovan Blagojevic; Simone Fatichi (Science of The Total Environment, 2024)

Temperature controls the relation between soil organic carbon and microbial carbon use efficiency - Zhaoyang Luo; Jianning Ren; Stefano Manzoni; Simone Fatichi (Global Change Biology, 2024)
Microbial carbon use efficiency (CUE) is an important variable mediating microbial effects on soil organic carbon (SOC) since it summarizes how much carbon is used for microbial growth or is respired. Yet, the role of CUE in regulating SOC storage remains debated, with evidence for both positive and negative SOC‐CUE relations. Here, we use a combination of measured data around the world and numerical simulations to explore SOC‐CUE relations accounting for temperature (T) effects on CUE. Results reveal that the sign of the CUE‐T relation controls the direction of the SOC‐CUE relations. A negative CUE‐T relation leads to a positive SOC‐CUE relation and vice versa, highlighting that CUE‐T patterns significantly affect how organic carbon is used by microbes and hence SOC‐CUE relations. Numerical results also confirm the observed negative SOC‐T relation, regardless of the CUE‐T patterns, implying that temperature plays a more dominant role than CUE in controlling SOC storage. The SOC‐CUE relation is usually negative when temperature effects are isolated, even though it can become positive when nonlinear microbial turnover is considered. These results indicate a dominant role of CUE‐T patterns in controlling the SOC‐CUE relation. Our findings help to better understand SOC and microbial responses to a warming climate.

When do plant hydraulics matter in terrestrial biosphere modelling? - Athanasios Paschalis; Martin G. De Kauwe; Manon Sabot; Simone Fatichi (Global Change Biology, 2024)
The ascent of water from the soil to the leaves of vascular plants, described by the study of plant hydraulics, regulates ecosystem responses to environmental forcing and recovery from stress periods. Several approaches to model plant hydraulics have been proposed. In this study, we introduce four different versions of plant hydraulics representations in the terrestrial biosphere model T&C to understand the significance of plant hydraulics to ecosystem functioning. We tested representations of plant hydraulics, investigating plant water capacitance, and long‐term xylem damages following drought. The four models we tested were a combination of representations including or neglecting capacitance and including or neglecting xylem damage legacies. Using the models at six case studies spanning semiarid to tropical ecosystems, we quantify how plant xylem flow, plant water storage and long‐term xylem damage can modulate overall water and carbon dynamics across multiple time scales. We show that as drought develops, models with plant hydraulics predict a slower onset of plant water stress, and a diurnal variability of water and carbon fluxes closer to observations. Plant water storage was found to be particularly important for the diurnal dynamics of water and carbon fluxes, with models that include plant water capacitance yielding better results. Models including permanent damage to conducting plant tissues show an additional significant drought legacy effect, limiting plant productivity during the recovery phase following major droughts. However, when considering ecosystem responses to the observed climate variability, plant hydraulic modules alone cannot significantly improve the overall model performance, even though they reproduce more realistic water and carbon dynamics. This opens new avenues for model development, explicitly linking plant hydraulics with additional ecosystem processes, such as plant phenology and improved carbon allocation algorithms.

Aerodynamic effects cause higher forest evapotranspiration and water yield reductions after wildfires in tall forests - Naika Meili; Jason Beringer; Jiacheng Zhao; Simone Fatichi (Global Change Biology, 2024)
Wildfires are increasing in frequency, intensity, and extent globally due to climate change and they can alter forest composition, structure, and function. The destruction and subsequent regrowth of young vegetation can modify the ecosystem evapotranspiration and downstream water availability. However, the response of forest recovery on hydrology is not well known with even the sign of evapotranspiration and water yield changes following forest fires being uncertain across the globe. Here, we quantify the effects of forest regrowth after catastrophic wildfires on evapotranspiration and runoff in the world's tallest angiosperm forest ( Eucalyptus regnans ) in Australia. We combine eddy covariance measurements including pre‐ and post‐fire periods, mechanistic ecohydrological modeling and then extend the analysis spatially to multiple fires in eucalypt‐dominated forests in south‐eastern Australia by utilizing remote sensing. We find a fast recovery of evapotranspiration which reaches and exceeds pre‐fire values within 2 years after the bushfire, a result confirmed by eddy covariance data, remote sensing, and modeling. Such a fast evapotranspiration recovery is likely generalizable to tall eucalypt forests in south‐eastern Australia as shown by remote sensing. Once climate variability is discounted, ecohydrological modeling shows evapotranspiration rates from the recovering forest which reach peak values of +20% evapotranspiration 3 years post‐fire. As a result, modeled runoff decreases substantially. Contrary to previous research, we find that the increase in modeled evapotranspiration is largely caused by the aerodynamic effects of a much shorter forest height leading to higher surface temperature, higher humidity gradients and therefore increased transpiration. However, increases in evapotranspiration as well as decreases in runoff caused by the young forest are constrained by energy and water limitations. Our result of an increase in evapotranspiration due to aerodynamic warming in a shorter forest after wildfires could occur in many parts of the world experiencing forest disturbances.

Effects of tree plantings with varying street aspect ratios on the thermal environment using a mechanistic urban canopy model - Taihan Chen; Naika Meili; Simone Fatichi; Jian Hang; Puay Yok Tan; Chao Yuan (Building and Environment, 2023)

Satellite‐based evidence highlights a considerable increase of urban tree cooling benefits from 2000 to 2015 - Jiacheng Zhao; Xiang Zhao; Donghai Wu; Naika Meili; Simone Fatichi (Global Change Biology, 2023)
Tree planting is a prevalent strategy to mitigate urban heat. Tree cooling efficiency (TCE), defined as the temperature reduction for a 1% tree cover increase, plays an important role in urban climate as it regulates the capacity of trees to alter the surface energy and water budget. However, the spatial variation and more importantly, temporal heterogeneity of TCE in global cities are not fully explored. Here, we used Landsat‐based tree cover and land surface temperature (LST) to compare TCEs at a reference air temperature and tree cover level across 806 global cities and to explore their potential drivers with a boosted regression tree (BRT) machine learning model. From the results, we found that TCE is spatially regulated by not only leaf area index (LAI) but climate variables and anthropogenic factors especially city albedo, without a specific variable dominating the others. However, such spatial difference is attenuated by the decrease of TCE with tree cover, most pronounced in midlatitude cities. During the period 2000–2015, more than 90% of analyzed cities showed an increasing trend in TCE, which is likely explained by a combined result of the increase in LAI, intensified solar radiation due to decreased aerosol content, increase in urban vapor pressure deficit (VPD) and decrease of city albedo. Concurrently, significant urban afforestation occurred across many cities showing a global city‐scale mean tree cover increase of 5.3 ± 3.8% from 2000 to 2015. Over the growing season, such increases combined with an increasing TCE were estimated to on average yield a midday surface cooling of 1.5 ± 1.3°C in tree‐covered urban areas. These results are offering new insights into the use of urban afforestation as an adaptation to global warming and urban planners may leverage them to provide more cooling benefits if trees are primarily planted for this purpose.

Environmental changes promoted vegetation growth and reduced water yield over the temperate semi-arid grassland of China during 1901–2016 - Xinxin Pang; Simone Fatichi; Huimin Lei; Zhentao Cong; Hanbo Yang; Limin Duan (Journal of Hydrology, 2023)

Gross primary productivity and water use efficiency are increasing in a high rainfall tropical savanna - Lindsay B. Hutley; Jason Beringer; Simone Fatichi; Stanislaus J. Schymanski; Matthew Northwood (Global Change Biology, 2022)
Despite their size and contribution to the global carbon cycle, we have limited understanding of tropical savannas and their current trajectory with climate change and anthropogenic pressures. Here we examined interannual variability and externally forced long‐term changes in carbon and water exchange from a high rainfall savanna site in the seasonal tropics of north Australia. We used an 18‐year flux data time series (2001–2019) to detect trends and drivers of fluxes of carbon and water. Significant positive trends in gross primary productivity (GPP, 15.4 g C m 2 year −2 ), ecosystem respiration ( R eco , 8.0 g C m 2 year −2 ), net ecosystem productivity (NEE, 7.4 g C m 2 year −2 ) and ecosystem water use efficiency (WUE, 0.0077 g C kg H 2 O −1 year −1 ) were computed. There was a weaker, non‐significant trend in latent energy exchange (LE, 0.34 W m −2 year −1 ). Rainfall from a nearby site increased statistically over a 45‐year period during the observation period. To examine the dominant drivers of changes in GPP and WUE, we used a random forest approach and a terrestrial biosphere model to conduct an attribution experiment. Radiant energy was the dominant driver of wet season fluxes, whereas soil water content dominated dry season fluxes. The model attribution suggested that [CO 2 ], precipitation and T air accounting for 90% of the modelled trend in GPP and WUE. Positive trends in fluxes were largest in the dry season implying tree components were a larger contributor than the grassy understorey. Fluxes and environmental drivers were not significant during the wet season, the period when grasses are active. The site is potentially still recovering from a cyclone 45 years ago and regrowth from this event may also be contributing to the observed trends in sequestration, highlighting the need to understand fluxes and their drivers from sub‐diurnal to decadal scales.

Can we replace observed forcing with weather generator in land surface modeling? Insights from long-term simulations at two contrasting boreal sites - Marco Alves; Daniel F. Nadeau; Biljana Music; François Anctil; Simone Fatichi (Theoretical and Applied Climatology, 2021)

A review of studies on observed precipitation trends in Italy - Enrica Caporali; Marco Lompi; Tommaso Pacetti; Valentina Chiarello; Simone Fatichi (International Journal of Climatology, 2021)
Research to detect changes in precipitation variables has become a topic of particular interest to understand modifications in water resources availability. The review is focused on the Italian territory, outlining the “state of the art” of changes in precipitation regime through a review of 54 published studies on observed rainfall trend analyses, in the period 1999–2018. The aim is to combine a large body of knowledge in a single review and to explain the main patterns of rainfall changes occurred in Italy over the last decades. The analysis focused on the Total Precipitation (TP) and the number of Wet Days (WDs) indices at the annual and seasonal scale. A weight factor is introduced to take into account the differences among studies in geographical area, time series length, and number of stations. The review is accompanied by the discussion of other rainfall related variables, that is, precipitation intensity, extreme rainfall events and meteorological droughts, which are useful to provide a broader picture of rainfall changes. Overall, there is an agreement about the tendency of a decrease in wet days on the entire Italy, with limited discrepancies in the various regions. A decrease in wet days is accompanied by a negative trend (although less evident) in total precipitation, especially in winter. Nevertheless, a univocal direction of trends (or lack of thereof) in annual total precipitation and mostly hydrological extreme events is difficult to achieve.

Downscaling climate projections over large and data sparse regions: Methodological application in the Zambezi River Basin - Nadav Peleg; Scott Sinclair; Simone Fatichi; Paolo Burlando (International Journal of Climatology, 2020)
Climate impact studies often require climate data at a higher space–time resolution than is available from global and regional climate models. Weather generator (WG) models, generally designed for mesoscale applications (e.g., 10 1 –10 5 km 2 ), are popular and widely used tools to downscale climate data to finer resolution. One advantage of using WGs is their ability to generate the necessary climate variables for impact studies in data sparse regions. In this study, we evaluate the ability of a previously established state of the art WG (the AWE‐GEN‐2d model) to perform in data sparse regions that are beyond the mesoscale, using the Zambezi River basin (10 6 km 2 ) in southeast Africa as a case study. The AWE‐GEN‐2d model was calibrated using data from satellite retrievals and climate re‐analysis products in place of the absent observational data. An 8‐km climate ensemble at hourly resolution, covering the period of 1976–2099 (present climate and RCP4.5 emission scenario from 2020), was then simulated. Using the simulated 30‐member ensemble, climate indices for both present and future climates were computed. The high‐resolution climate indices allow detailed analysis of the effects of climate change on different areas within the basin. For example, the southwestern area of the basin is predicted to experience the greatest change due to increased temperature, while the southeastern area was found to be already so hot that is less affected (e.g., the number of 'very hot days' per year increase by 18 and 9 days, respectively). Rainfall intensities are found to increase most in the eastern areas of the basin (1 mm·d −1 ) in comparison to the western region (0.3 mm·d −1 ). As demonstrated in this study, AWE‐GEN‐2d can be calibrated successfully using data from climate reanalysis products in the absence of ground station data and can be applied at larger scales than the mesoscale.

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

On the use of observations in assessment of multi-model climate ensemble - Donghui Xu; Valeriy Y. Ivanov; Jongho Kim; Simone Fatichi (Stochastic Environmental Research and Risk Assessment, 2019)

Climate change and uncertainty assessment over a hydroclimatic transect of Michigan - Jongho Kim; Valeriy Y. Ivanov; Simone Fatichi (Stochastic Environmental Research and Risk Assessment, 2016)

A comprehensive analysis of changes in precipitation regime in Tuscany - Simone Fatichi; Enrica Caporali (International Journal of Climatology, 2009)
The analysis of changes in precipitation is nowadays of great interest because rainfall space‐time distribution is considered one of the most important indexes in the natural climatic cycle. This study proposes an investigation of precipitation time series recorded in the region of Tuscany (Central Italy) in the period 1916–2003. Forty indexes are defined to evaluate changes in the precipitation patterns and trend detection is performed through statistical tests to assess the significance of temporal and spatial changes in the precipitation regime. The presented analysis does not show strong evidence of nonstationarity. A few indexes in a given number of stations of the analysed territory do show a slight trend, but the significance of those trends is lost once the multiple location testing issue is considered. The complexity of the climate in central Italy, i.e. the presence of numerous feedbacks might in fact distort or remove the consequences of global warming on the precipitation regime. Copyright © 2009 Royal Meteorological Society